622.692 RESEARCH OF CORROSION AND FOAMING PROCESSES IN GAS ABSORPTION PURIFICATION AND TECHNOLOGY OF THEIR PROTECTION IN INHIBITORS - Sattorov, Mirvohid; Panoev, Erali (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract: Objective. The article presents the results of scientific studies of corrosion inhibitors synthesized on the basis of local raw materials in technological devices and information about the technological processes of inhibition. The adsorption and mechanism of action of the synthesized corrosion inhibitor TFO on metals were studied. Based on the results of the study, a technological scheme for the use of the corrosion inhibitor TFO in the technological devices of the Gazli Gas Processing Plant was recommended in order to sharply slow down corrosion. Methods. Corrosion studies were carried out by gravimetric method in different metal brands and in different environments. Results. The synthesized TFO corrosion inhibitor showed 93.8% protection efficiency at 100 mg/l at different concentrations. Conclusion. The inhibitor formed a very thin layer on the metal surface and created conditions for its protection against corrosion in the external environment.